(untitled) (Bioagro, 2020)
The wide diversity of species and varieties of chilies existing in Mexico demands the determination of their antioxidant properties to be recommended as food of high nutraceutical value, so far unknown in most chilies species, especially when the fruits are dehydrated. This information may provide economic alternatives to the producer and promote more efficient agro-industrial use of the fruits. The objective of the study was to evaluate the content of ascorbic acid, phenolic compounds, flavonoids, β-carotene and antioxidant activity of fruits of Capsicum annuum L. cultivar chili ancho, at two maturity stages of fresh and dehydrated chili. Results demonstrate that it is convenient to harvest shortly before horticultural maturity occurs so as to take advantage of the high content of ascorbic acid and DPPH radical scavenging. The content of phenolic compounds and flavonoids in the mature dehydrated (MD) chili was higher (898.58 and 345.78 mg∙100 g-1 DW, respectively) compared with the premature fresh chili (PMF), mature fresh (MF) and premature dehydrated (PMD). Significant differences were found in the content of β-carotene between the treatments PMF and MF (5.8 and 27.1 μg·g-1DW) and the treatments PMD and MD (347.8 and 483.0 μg·g-1 DW, respectively). Opposite effect was observed in the ascorbic acid content. The antioxidant activity of the chili PMF was significantly higher than that of MD. The process of dehydration did not affect the antioxidant activity in the premature chilies, nor in the mature ones. These nutraceutical characteristics provide an added value to the product.